The Effect of Sustainability Report Disclosure and Firm Size on Firm Value with Profitability as a Moderating Variable: A Study of Mining Companies in Indonesia - Sheilla Sonnya; Nurhastuty Kesumo Wardhani (Manunggal Halim Jaya, 2026)
This study examines the effect of sustainability report disclosure and firm size on firm value, with profitability as a moderating variable. A quantitative approach was employed, using secondary data obtained from financial statements, annual reports, and sustainability reports of mining companies listed on the Indonesia Stock Exchange (IDX), as well as information from the companies’ official websites, covering the period 2021–2023. Firm value was measured using Tobin’s Q ratio, sustainability report disclosure was assessed through the Sustainability Report Disclosure Index (SRDI) based on GRI standards, firm size was proxied by the natural logarithm of total assets, and profitability was measured using return on assets (ROA). The findings reveal that sustainability report disclosure does not have a significant effect on firm value, whereas firm size exerts a positive and significant effect. Moreover, profitability does not moderate the relationship between sustainability report disclosure and firm value, but it does strengthen the relationship between firm size and firm value in the mining sector. The findings imply that companies should enhance the quality of sustainability reports and integrate them into core business strategies, while investors are advised to evaluate both profitability and report quality for better insights into firm value. Future research may expand samples, extend periods, or explore other industries for comparison.